Penerapan Model RIBASIM untuk Optimalisasi Pengalokasian Sumber Daya Air - Sulwan Permana; Denny Firmansah (Institut Teknologi Garut, 2026)
This study discusses the pressure on water availability resulting from population growth, increased economic activities, and changes in river discharge. These conditions create an imbalance between water supply and demand, highlighting the need for more planned and systematic water management. The objective of this research is to optimize the utilization and allocation of water resources in order to meet community needs in an equitable and sustainable manner. The method employed is a quantitative approach using the RIBASIM (River Basin Simulation Model). The research stages include collecting data on water availability and demand, developing management scenarios, and conducting simulations and result analyses to assess system reliability. The novelty of this study lies in the application of RIBASIM as an integrated water allocation optimization tool, utilizing adaptive scenarios to enhance distribution reliability in regions with high discharge variability. The RIBASIM model is used to evaluate how effectively water can be allocated to various sectors such as irrigation, public water supply, and industry. The results indicate discrepancies between water availability and demand that lead to reduced service levels in several sectors. After simulations and the implementation of strategies such as prioritizing water use, adjusting cropping patterns, applying rotational water distribution, and reusing wastewater, the reliability of the water management system improved. Overall, this study demonstrates that the use of the RIBASIM model can support more efficient planning and decision-making in water allocation. This model-based approach supports integrated and sustainable water resource management and can serve as a foundation for enhancing water security and community welfare in the future.